EFEKTIVITAS POJOK BACA DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI YAYASAN GAMMA INDONESIA - Tsabit, Muhammad Luthfan; Apriani, Dina; Ardiansyah, Leo; Malik, Anastasia Maulina; Arlita, Rusi Sari; Tantri, Rika Tri; Ardiansyah, Rendi; Nuraini, Siti Rahma; Yuliasari, Putri Riski; Saputra, Wahyu Aji; et al. (Batara Wisnu : Indonesian Journal of Community Services, 2025)
Real Work Lecture (KKN) activities carried out by the ITB Ahmad Dahlan Jakarta Group 19 KKN Team at the Gamma Indonesia Foundation aim to improve the quality of children’s learning through the construction of a reading corner. The methods used in this activity include observation, problem mapping, planning, implementing activities, and preparing reports. The result of this activity was the successful construction of a comfortable and attractive reading corner, equipped with various books and wall decorations that attract children’s attention. It is hoped that this reading corner can support the foundation’s education program by increasing children’s interest in reading and the quality of their learning. Apart from that, the socialization and donation activities carried out by students also succeeded in strengthening relationships between students, children and foundation administrators. It is recommended that the Gamma Indonesia Foundation can maximize the function of the reading corner by scheduling regular reading activities and making continuous improvements. This activity is expected to have a long-term positive impact on the development of children’s literacy at the Gamma Indonesia Foundation, as well as encouraging sustainable collaboration between the foundation and the campus for educational progress.